Complex Fibonacci $p$-Numbers - Tasci, Dursun; Yalcin, Feyza (Communications in Mathematics and Applications, 2014)
In the present paper, the complex Fibonacci $p$-numbers are defined by two-dimensional recurrence relation and some results are obtained.
Keywords: Complex Fibonacci $p$-numbers; Complex Fibonacci numbers; Fibonacci $p$-numbers